RISK FACTORS ANALYSIS OF WORK FATIGUE AMONG ONLINE MOTORCYCLE DRIVERS IN SOUTH TANGERANG CITY - Rahmawati, Rani (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
Online motorcycle taxi drivers are one the road users, it is important to obey traffic regulations. In UU No. 22 2009 it is mentioned that the driver of the vehicle must be conscious and not distracted because of tiredness, this situation can cause traffic accidents if forced to keep driving. The purpose of this study is to analyze what factors are related to work fatigue that occurs in online drivers in South Tangerang City in 2022. The research method used in this study is a literature review. The data used are secondary data from scientific articles/journals, books, and documents. Search literature on internet sites such as Scopus, Google Scholar, Garuda, and College Journals. The research was conducted on 3 international articles and 2 national articles. The results of the study based on these five articles, after summarizing the findings of ten (10) risk factors related to work fatigue in online motorcycle taxi drivers, namely age, duration of work, total distance achieved, history of illness, length of sleep, over time, work stress, lack of physical activity, and marital status. This research is recommended for companies to further improve the welfare of online motorcycle taxi drivers by reducing income deductions, calculating basic costs and authorized capital issued by online motorcycle taxi drivers, there are some complaints by online motorcycle taxi drivers, namely working unhealthy in pursuit of bonuses, this has an impact on working hours that are too high so that it can cause work fatigue for online motorcycle taxi drivers.